Glass, preparation method and application thereof, cover plate structure and electronic device

By using glass with high Young's modulus and moderate surface roughness, the problem of crease in the bent area of ​​the screen of foldable electronic devices is solved, better impact resistance and optical performance are achieved, and the display aesthetics of the equipment is improved.

CN118108414BActive Publication Date: 2025-04-04HONOR DEVICE CO LTD

Patent Information

Application Number
CN202211517462.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-04-04
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

The screen bent areas of existing foldable electronic devices are prone to creases, affecting the aesthetics of the display.

Method used

Glass with a Young's modulus greater than or equal to 90 GPa, and the surface roughness in its thickness direction is set to 3nm~100 nm to improve adhesion and optical properties and reduce creases.

Benefits of technology

Effectively reduce the creases in the bent area of ​​the screen, improve the impact resistance and optical performance of glass, and improve the display aesthetics of electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118108414B_ABST
    Figure CN118108414B_ABST
Patent Text Reader

Abstract

The present application discloses a glass and a preparation method and application thereof, a cover plate structure and an electronic device, which relate to the field of display technology and are used to reduce creases in the bending area of ​​the screen. The glass comprises a first surface and a second surface arranged opposite to each other in the thickness direction thereof, the surface roughness of at least one of the first surface and the second surface is greater than or equal to 3nm and less than or equal to 100nm, and the Young's modulus of the glass is greater than or equal to 90GPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display technology, and in particular to a glass and a preparation method and application thereof, a cover plate structure and an electronic device. Background Art

[0002] With the development of electronic products, foldable electronic devices, as a new form of electronic terminal products, are favored by more and more consumers due to their advantages such as bendability and portability.

[0003] As an important component of foldable electronic devices, the display aesthetics of the screen seriously affects consumers' choice of foldable electronic devices. At present, the crease in the bending area of ​​the screen is a major pain point that affects the display aesthetics of the screen. Therefore, how to reduce the crease in the bending area of ​​the screen has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] Embodiments of the present application provide a glass and a preparation method and application thereof, a cover plate structure and an electronic device for reducing creases in the bending area of ​​a screen.

[0005] To achieve the above objectives, the embodiments of the present application adopt the following technical solutions:

[0006] In a first aspect, the present application provides a glass comprising a first surface and a second surface arranged opposite to each other in a thickness direction thereof, wherein the surface roughness of at least one of the first surface and the second surface is greater than or equal to 3 nm and less than or equal to 100 nm, and the Young's modulus of the glass is greater than or equal to 90 GPa.

[0007] The glass in the embodiment of the present application, by setting the surface roughness Ra of the first surface and / or the second surface to 3nm~100nm, can increase the adhesion between the first surface and / or the second surface and the organic material, reduce or even avoid the risk of the organic material attached to the first surface and / or the second surface peeling off from the first surface and / or the second surface, thereby slowing down the deformation of the organic material during the folding process, and further reducing the creases of the cover plate structure and the screen. In addition, by setting the surface roughness Ra of the first surface and / or the second surface to 3nm~100nm, the haze of the glass can be reduced, the transmittance of the glass can be improved, the optical properties of the glass can be guaranteed, and further the optical properties of the cover plate structure can be guaranteed. In addition, the glass in the embodiment of the present application, by setting the Young's modulus of the glass to be greater than or equal to 90GPa, can improve the rigidity and impact resistance of the glass, which is beneficial to reduce the deformation of the glass, improve the ability of the cover plate structure to resist deformation and the ability of the cover plate structure to recover to its original state after deformation, can reduce the creases in the bending area of ​​the screen, and can better protect the screen.

[0008] In a possible implementation of the first aspect, the surface roughness of at least one of the first surface and the second surface is greater than or equal to 15 nm and less than or equal to 80 nm. In this way, while ensuring the optical properties of the glass, the adhesion between the first surface and / or the second surface and the organic material can be further increased, thereby further slowing down the deformation of the organic material during the folding process, and further reducing the creases of the cover structure and the screen.

[0009] In a possible implementation of the first aspect, the glass is microcrystalline glass. In this way, the glass can have a higher Young's modulus, which is conducive to further improving the rigidity of the glass, thereby further improving the ability of the glass and cover plate structure to resist deformation and the ability of the glass and cover plate structure to recover to their original state after deformation, thereby reducing creases in the bending area of ​​the screen.

[0010] In a possible implementation of the first aspect, the glass-ceramics includes a main crystalline phase, and the main crystalline phase is one or more of spodumene, petalite, lithium silicate, lithium disilicate, β-quartz, zirconium oxide, spinel, and gahnite. In this way, the optical properties of the glass-ceramics can be guaranteed while the mechanical properties of the glass-ceramics are guaranteed, and the processing difficulty of the glass-ceramics can be reduced.

[0011] In a possible implementation of the first aspect, the microcrystalline glass includes a main crystalline phase, the mass fraction of the main crystalline phase is greater than or equal to 50%, and the main crystalline phase is a crystalline phase with a relatively obvious peak shape in the glass X-ray diffraction spectrum (XRD). Among them, the mass fraction of the main crystalline phase is equal to the mass of the main crystalline phase divided by the sum of the masses of all crystalline phases in the microcrystalline glass (also called the mass of the total crystalline phase). Exemplarily, the mass fraction of the main crystalline phase can be 50%, 55%, 60%, 65%, 70%, 75%, 78%, 80%, 82%, 83%, 85%, etc. In this way, by controlling the mass fraction of the main crystalline phase to be not less than 50%, the purity of the main crystalline phase can be improved, and the number of scatterings between different crystalline phases can be reduced, so that the transmittance of the microcrystalline glass can be improved, the haze of the microcrystalline glass can be reduced, and the optical properties of the microcrystalline glass can be improved, which is beneficial to improve the optical properties of the glass, the cover plate structure and the screen.

[0012] In a possible implementation of the first aspect, the average crystal grain size of the microcrystalline glass is greater than or equal to 5 nm and less than or equal to 80 nm. Thus, by controlling the average crystal grain size of the microcrystalline glass to be greater than or equal to 5 nm and less than or equal to 80 nm, the optical performance and drop resistance of the microcrystalline glass can be taken into account, thereby ensuring the optical performance and drop resistance of the glass.

[0013] In a possible implementation manner of the first aspect, an average grain size of a crystal phase of the microcrystalline glass is greater than or equal to 5 nm and less than or equal to 60 nm.

[0014] In a possible implementation manner of the first aspect, an average grain size of a crystal phase of the microcrystalline glass is greater than or equal to 5 nm and less than or equal to 40 nm.

[0015] In a possible implementation manner of the first aspect, an average grain size of a crystal phase of the microcrystalline glass is greater than or equal to 5 nm and less than or equal to 30 nm.

[0016] In a possible implementation of the first aspect, the thickness of the glass is greater than or equal to 0.02 mm and less than or equal to 0.1 mm. For example, the thickness of the glass may be 0.02 mm, 0.03 mm, 0.04 mm, 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm, 0.1 mm, etc. In this way, both the bending performance and the mechanical strength of the glass can be taken into account.

[0017] In a possible implementation of the first aspect, the transmittance of the glass at a wavelength of 550 nm is greater than or equal to 89%. For example, the transmittance of the glass at a wavelength of 550 nm is 89%, 90%, 91%, 92%, etc. In this way, the glass and cover plate structure can be guaranteed to have excellent optical properties.

[0018] In a possible implementation of the first aspect, the pen drop height of the glass is greater than or equal to 20 mm. Exemplarily, the pen drop height of the glass is 20 mm, 21 mm, 22 mm, 23 mm, 24 mm, 25 mm, 26 mm, 27 mm, 28 mm, 29 mm, 30 mm, 31 mm, 32 mm, 35 mm, etc. In this way, the mechanical strength and impact resistance of the glass and cover plate structure can be improved.

[0019] In a possible implementation of the first aspect, the static limit bending diameter of the glass is less than or equal to (0.8Et+t) mm; wherein E is the Young's modulus of the glass, in GPa, and t is the thickness of the glass, in mm, and in the calculation formula, E and t are only numerical values, without taking the unit into account. In this way, the static bending performance of the glass can be guaranteed, the bending strength of the glass can be guaranteed, and creases in the bending area of ​​the cover plate structure and the screen can be reduced.

[0020] In a possible implementation of the first aspect, the number of times the glass is dynamically bent at a bending diameter of (Et+t) mm is greater than or equal to 200,000 times. Wherein, E is the Young's modulus of the glass, in GPa, and t is the thickness of the glass, in mm. In the calculation formula, E and t are only numerical values, and the units are not taken into account. In this way, the dynamic bending performance of the glass can be guaranteed.

[0021] In a possible implementation of the first aspect, the number of times the glass is dynamically bent at a bending diameter of (Et+t) mm is greater than or equal to 300,000 times. In this way, the dynamic bending performance of the glass can be further guaranteed.

[0022] In a possible implementation of the first aspect, an ion exchange layer is formed on the surface of the glass, which can further improve the mechanical properties of the glass and increase the hardness and deformation resistance of the glass.

[0023] In a possible implementation manner of the first aspect, the ion exchange layer includes a K ion exchange layer, and a depth of the K ion exchange layer is greater than or equal to 0.06t and less than or equal to 0.2t, where t is the thickness of the glass in mm.

[0024] In a possible implementation manner of the first aspect, the ion exchange layer includes a Na ion exchange layer, and a depth of the Na ion exchange layer is greater than or equal to 0.15t and less than or equal to 0.25t, where t is the thickness of the glass in mm.

[0025] In a possible implementation of the first aspect, the ultra-thin glass includes a side surface, the side surface is connected between the first surface and the second surface, and the side surface is a curved surface. In this way, the stress on the outer edge of the glass can be reduced, which is conducive to improving the bending strength of the glass, thereby facilitating further reducing the crease in the bending area of ​​the screen.

[0026] In a second aspect, the present application provides a method for preparing glass, the preparation method comprising: providing a glass substrate, the Young's modulus of the glass substrate being greater than or equal to 90 GPa; performing a thinning process on the glass substrate to thin the glass substrate to a target thickness to obtain a first glass, the first glass comprising a first surface and a second surface opposite to each other in a thickness direction thereof, the surface roughness of the first surface and / or the second surface being greater than or equal to 3 nm and less than or equal to 100 nm.

[0027] The method for preparing glass in the embodiment of the present application sets the Young's modulus of the glass substrate to be greater than or equal to 90 GPa, and controls the surface roughness Ra of the first surface and / or the second surface of the glass obtained after thinning treatment (that is, the first glass) to be greater than or equal to 3 nm and less than or equal to 100 nm. On the one hand, the rigidity and impact resistance of the prepared glass can be improved, which is beneficial to reducing the deformation of the glass, improving the ability of the cover structure including the glass to resist deformation and the ability of the cover structure to recover to its original state after deformation, and can reduce the creases in the bending area of ​​the screen and better protect the screen; on the other hand, while ensuring the optical properties of the glass, the adhesion between the surface of the glass (that is, the first surface and the second surface mentioned above) and the organic material is increased, and the risk of the organic material attached to the glass surface being peeled off from the glass is reduced or even avoided, thereby slowing down the deformation of the organic material during the folding process, and further reducing the creases of the cover structure and the screen. The preparation method is simple and easy to implement.

[0028] In a possible implementation manner of the second aspect, a method for thinning the glass substrate includes one or more of chemical thinning, mechanical grinding and polishing, and chemical mechanical polishing.

[0029] In a possible implementation of the second aspect, after obtaining the first glass, the preparation method further includes: performing edge processing on the first glass so that the side surface of the first glass is formed into a curved surface. In this way, the side surface of the glass obtained by the preparation method can be formed into a curved surface, which can reduce the edge stress of the glass, which is conducive to improving the bending strength of the glass, thereby facilitating further reducing the crease in the bending area of ​​the screen.

[0030] In a possible implementation manner of the second aspect, performing edge processing on the first glass includes: performing chemical etching processing on the edge of the first glass.

[0031] In a possible implementation manner of the second aspect, performing edge processing on the first glass includes: performing heat treatment on the first glass.

[0032] In a possible implementation of the second aspect, after the glass substrate is thinned and the first glass is obtained, the preparation method further includes: chemically strengthening the first glass to form an ion exchange layer on the surface of the first glass. By chemically strengthening the first glass, on the one hand, a certain compressive stress can be obtained on the surface of the obtained glass. When the glass is subjected to an external force, the compressive stress on its surface needs to be offset first, and then the glass is placed in a tension state, thereby improving the ability of the glass to resist external forces, and significantly improving the strength of the glass, thereby significantly improving the ability of the glass to resist deformation and the ability to recover to its original state after deformation, thereby reducing the creases in the bending area of ​​the screen and better protecting the screen; on the other hand, after the first glass is chemically strengthened, an ion exchange layer of a certain depth will be formed on the surface of the obtained glass, so that even if an external force forms a crack on the glass surface, the formed ion exchange layer will effectively eliminate or inhibit the further expansion of the crack, thereby greatly improving the ability of the glass to resist external forces and significantly enhancing the strength of the obtained glass.

[0033] In a possible implementation of the second aspect, after obtaining the first glass, the preparation method further includes: performing chemical polishing on the first glass, so as to improve the surface uniformity of the obtained glass and help further improve the mechanical strength of the glass.

[0034] In a third aspect, the present application provides a cover plate structure, which includes the glass in any of the above technical solutions.

[0035] In a possible implementation manner of the third aspect, the cover structure further includes: a protective layer, wherein the protective layer is fixedly connected to the first surface or the second surface of the glass.

[0036] In a possible implementation manner of the third aspect, a peeling force between the protective layer and the glass is greater than or equal to 18 N / cm.

[0037] In a possible implementation manner of the third aspect, the protective layer is fixedly connected to the glass by bonding with an optically transparent adhesive, or the protective layer is coated on the surface of the glass.

[0038] In a fourth aspect, the present application provides an electronic device, comprising: a screen, the screen comprising a display screen and a cover structure arranged in a stacked manner, the cover structure being located on the side facing the display surface of the display screen, and the cover structure being the cover structure of any of the above-mentioned technical solutions.

[0039] In a possible implementation manner of the fourth aspect, a peeling force between the display screen and the cover plate structure is greater than or equal to 18 N / cm.

[0040] In a possible implementation of the fourth aspect, the electronic device also includes a shell assembly, the shell assembly includes a first shell, a second shell and a hinge mechanism, the first shell is rotatably connected to one side of the hinge mechanism, and the second shell is rotatably connected to the other side of the hinge mechanism; the screen includes a first display area, a second display area and a third display area, the third display area is connected between the first display area and the second display area, the first display area is arranged on the first shell, the second display area is arranged on the second shell, and the third display area is arranged on the hinge mechanism.

[0041] In a fifth aspect, the present application provides an application of glass according to any of the above technical solutions or glass prepared by the preparation method of any of the above technical solutions in cover structures, screens, and electronic devices.

[0042] Among them, the technical effects brought about by any design method in the second to fifth aspects can refer to the technical effects brought about by different design methods in the first aspect, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 A perspective view of an electronic device provided for some embodiments of the present application;

[0044] Figure 2 for Figure 1 A schematic diagram of a partial exploded structure of the electronic device shown;

[0045] Figure 3 for Figure 1 A schematic diagram of the structure of the electronic device shown in the folded state;

[0046] Figure 4 A cross-sectional view of a screen in an electronic device provided in some embodiments of the present application;

[0047] Figure 5 A schematic diagram of a laminated structure of a cover plate structure provided in some embodiments of the present application;

[0048] Figure 6 A schematic diagram of the structure of glass provided in some embodiments of the present application;

[0049] Figure 7a for Figure 6 Schematic diagram of the structure of the glass shown at different display ratios;

[0050] Figure 7b Schematic diagrams of microstructures provided for other embodiments of the present application;

[0051] Figure 8 For scanning using atomic force microscopy (AFM) Figure 6 A scan image obtained from a first surface of the glass shown;

[0052] Fig. 9 A schematic diagram of glass in a bent state provided in some embodiments of the present application;

[0053] Fig.10 A flow chart of a method for preparing glass provided in some embodiments of the present application;

[0054] Fig.11 A flow chart of a method for preparing glass provided in some other embodiments of the present application;

[0055] Fig.12 A flow chart of a method for preparing glass provided in some other embodiments of the present application;

[0056] Fig.13 A flow chart of a method for preparing glass provided in some other embodiments of the present application;

[0057] Fig.14 Schematic diagram of the stacked structure of the screen provided in some embodiments of the present application.

[0058] Reference numerals:

[0059] 100. Electronic equipment;

[0060] 10. Shell assembly; 11. First shell; 12. Second shell; 13. Rotating shaft mechanism;

[0061] 20. screen; 21. first display area; 22. second display area; 23. third display area;

[0062] 201. Support structure;

[0063] 202, display screen; 202a, display surface;

[0064] 203, cover plate structure; 203a, main body layer; 203b, protective layer;

[0065] 204, glass; 204a, first surface; 204b, second surface; 204c, side surface; 204d, microstructure; 204e, ion exchange layer; 2041, first part; 2042, second part; 2043, third part;

[0066] 204A, first glass; 204B, second glass; 204C, third glass;

[0067] 205, glass substrate; 205a, first surface; 205b, second surface;

[0068] 206, optically transparent adhesive;

[0069] 300. Protective film. DETAILED DESCRIPTION

[0070] In the embodiments of the present application, the terms "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.

[0071] In the embodiments of the present application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0072] In the description of the embodiments of the present application, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, at least one of a, b, or c can represent: a, b, c, ab, ac, bc, or abc, where a, b, c can be single or multiple.

[0073] In the description of the embodiments of the present application, "and / or" is only a description of the association relationship of the associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present application generally indicates that the associated objects before and after are in an "or" relationship.

[0074] In the description of the embodiments of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected" and "connected" should be understood in a broad sense. For example, "connection" can be a detachable connection or a non-detachable connection; it can be a direct connection or an indirect connection through an intermediate medium. Among them, "fixed connection" means that the two are connected to each other and the relative position relationship remains unchanged after the connection. "Rotational connection" means that the two are connected to each other and can rotate relative to each other after the connection. "Sliding connection" means that the two are connected to each other and can slide relative to each other after the connection.

[0075] The directional terms mentioned in the embodiments of the present application, such as "inside", "outside", "up", "down", "front", "back", "left", "right", etc., are only references to the directions of the drawings. Therefore, the directional terms used are for better and clearer explanation and understanding of the embodiments of the present application, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.

[0076] In the description of the embodiments of the present application, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device including the element.

[0077] The embodiment of the present application provides an electronic device, the cover structure of the electronic device includes glass. The electronic device in the embodiment of the present application can improve the impact resistance of the electronic device by setting the surface roughness of at least one of the two surfaces of the glass opposite to each other in the thickness direction (that is, the first surface and the second surface mentioned below) to 3nm~100nm, and setting the Young's modulus of the glass to be greater than or equal to 90GPa, and when the electronic device is a foldable electronic device, it can also effectively reduce the creases generated when the electronic device is bent.

[0078] Specifically, the electronic devices in the embodiments of the present application include but are not limited to mobile phones, tablet computers (tablet personal computers), laptop computers (laptop computers), personal digital assistants (PDAs), personal computers, notebook computers, vehicle-mounted devices, wearable devices, walkmans, radios, etc. Among them, wearable devices include but are not limited to smart bracelets, smart watches, smart head-mounted displays, smart glasses, etc.

[0079] The electronic device may be a foldable electronic device. For a foldable electronic device, under different usage requirements, the foldable electronic device may be unfolded to an unfolded state or folded to a folded state. Of course, the electronic device may also be a non-foldable electronic device. This embodiment and the following embodiments are exemplified by taking the electronic device as a foldable electronic device. Specifically, the foldable electronic device may be a foldable mobile phone.

[0080] See also Figure 1 and Figure 2 , Figure 1 A three-dimensional diagram of an electronic device 100 provided in some embodiments of the present application, wherein: Figure 1 The electronic device 100 is shown in an unfolded state. Figure 2 for Figure 1 The electronic device 100 is a schematic diagram of a partial exploded structure. The electronic device 100 includes a housing assembly 10 and a screen 20. It can be understood that Figure 1 Only some components of the electronic device 100 are schematically shown, and the actual shapes, sizes, positions and structures of these components are not subject to the present invention. Figure 1 restrictions.

[0081] The housing assembly 10 is used to protect the internal electronic components of the electronic device 100 and to carry the screen 20. Figure 1-Figure 2 The housing assembly 10 includes a first housing 11, a second housing 12 and a hinge mechanism 13. The hinge mechanism 13 is connected between the first housing 11 and the second housing 12. The first housing 11 and the second housing 12 are rotatably connected through the hinge mechanism 13, so that the first housing 11 and the second housing 12 can rotate relative to each other, so as to support the screen 20 to fold between the unfolded state and the folded state. The first housing 11 forms a first accommodating cavity ( Figure 1-Figure 2 The interior of the second housing 12 forms a second accommodating cavity ( Figure 1-Figure 2 The first accommodating chamber and the second accommodating chamber are used to accommodate electronic components such as a circuit board, a camera module, a speaker module, and a battery of the electronic device 100.

[0082] The screen 20 is used to display information and provide an interactive interface for the user. The screen 20 in this embodiment can be switched between an unfolded state and a folded state. Figure 1-Figure 2 The screen 20 includes a first display area 21, a second display area 22 and a third display area 23, and the third display area 23 is connected between the first display area 21 and the second display area 22. The first display area 21 is covered by the first shell 11, the second display area 22 is covered by the second shell 12, and the third display area 23 is covered by the hinge mechanism 13.

[0083] At least the third display area 23 of the screen 20 is made of a flexible material. The first display area 21 and the second display area 22 can be made of a flexible material, or a rigid material, or partially made of a rigid material and partially made of a flexible material, which is not specifically limited here. In some embodiments, the entire screen 20 is made of a flexible material, which is convenient to manufacture and has a low cost.

[0084] See also Figure 1When the electronic device 100 is in the unfolded state, the first display area 21, the second display area 22 and the third display area 23 of the screen 20 are arranged in the same plane and face the same direction. In this state, a large screen display can be achieved, which can provide users with richer information and bring users a better user experience.

[0085] See also Figure 3 , Figure 3 for Figure 1 A schematic diagram of the structure of the electronic device 100 shown in the folded state. When the electronic device 100 is in the folded state, the screen 20 is also in the folded state. Specifically, the third display area 23 of the screen 20 is in a bent state, the first display area 21 and the second display area 22 are approximately parallel and opposite to each other, and the shell assembly 10 is between the first display area 21 and the second display area 22. That is, the angle between the first display area 21 and the second display area 22 is 360° or approximately 360°, and the angle between the first shell 11 and the second shell 12 is also 360° or approximately 360°. In this state, the electronic device 100 is small in size and easy to carry, and a small screen display can be achieved with the help of at least one of the first display area 21 and the second display area 22.

[0086] When the electronic device 100 in this embodiment is in a folded state, the screen 20 is located outside the housing assembly 10. In this case, the foldable mobile phone is an inward-folding mobile phone. In other embodiments, when the electronic device 100 is in a folded state, the housing assembly 10 can also be protected outside the screen 20, and the screen 20 is invisible to the user. In this case, the foldable mobile phone is an inward-folding mobile phone. In this way, the size of the electronic device 100 can also be reduced, which is convenient for storage and carrying of the electronic device 100, and the screen 20 can be prevented from being scratched by hard objects.

[0087] See also Figure 4 , Figure 4 A cross-sectional view of a screen 20 in an electronic device 100 provided in some embodiments of the present application. The screen 20 includes a support structure 201, a display screen 202, and a cover structure 203 arranged in a stacked manner. The "stacked arrangement" described in the embodiments of the present application refers to the stacking of the various layer structures along the thickness direction of the layer structure. At this time, the various layer structures can be stacked in direct contact with each other, or can be interspersed with other layer structures.

[0088] The display screen 202 is used to display information such as images and videos. Specifically, the display screen 202 has a display surface 202a for displaying image information, and the display surface 202a of the display screen 202 is exposed to facilitate presenting information such as images and videos to the user. Exemplarily, the display screen 202 can be an organic light-emitting diode (OLED) display screen, an active-matrix organic light-emitting diode or an active-matrix organic light-emitting diode (AMOLED) display screen, a mini organic light-emitting diode (MIL-E) display screen, a micro organic light-emitting diode (MIL-E) display screen, a micro organic light-emitting diode (MIL-E) display screen, or a quantum dot light-emitting diode (QLED) display screen, etc.

[0089] The support structure 201 is arranged on the side of the display screen 202 that is opposite to the display surface 202a. The support structure 201 and the display screen 202 are stacked and fixedly connected by gluing or other methods. The support structure 201 is also called a bamboo book, which is used to increase the structural strength of the screen 20, and the support structure 201 can be folded together with the display screen 202. The support structure 201 can be in the form of a thin sheet, and the material of the support structure 201 includes but is not limited to metal and a composite material containing a fiber material.

[0090] The cover structure 203 is arranged on the side of the display screen 202 that the display surface 202a faces. The cover structure 203 is stacked with the display screen 202. The cover structure 203 can protect the display screen 202 and prevent dust, and the cover structure 203 can be folded together with the display screen 202. The cover structure 203 and the display screen 202 can be fixedly connected by an optically clear adhesive 206 (OCA). The optically clear adhesive 206 has the characteristics of being colorless and transparent, having high light transmittance, and having good bonding strength. It can be cured at room temperature or medium temperature, and has small curing shrinkage, etc., which can ensure the optical performance of the screen 20. The optically clear adhesive 206 may include one or more of silicone polymers, acrylic resins, unsaturated polyesters, polyurethanes, and epoxy resins.

[0091] In some embodiments, see Figure 5 , Figure 5Schematic diagram of the laminated structure of the cover plate structure 203 provided in some embodiments of the present application. The cover plate structure 203 includes a main layer 203a and a protective layer 203b which are laminated. The protective layer 203b is located on the side of the main layer 203a away from the display screen 202.

[0092] In some embodiments, in order to ensure the bending performance and optical performance of the cover structure 203, the material of the main layer 203a can be ultra-thin glass (UTG). Ultra-thin glass refers to glass with a thickness of less than 100 μm and flexibility, which can realize the bendable folding of the cover structure 203, and the ultra-thin glass has good optical properties and a high elastic modulus, can take into account the light transmittance and hardness of the cover structure 203, and has good crease self-repair ability, which is conducive to reducing the crease of the screen 20.

[0093] See also Figure 5 , the protective layer 203b is fixedly connected to the surface of the main layer 203a on the side facing away from the display screen 202. The protective layer 203b is used to protect the main layer 203a, and can prevent scratches on the main layer 203a. In addition, the protective layer 203b can also reduce the probability of the main layer 203a being broken due to impact and the probability of glass fragments splashing after breaking. In some embodiments, the protective layer 203b can be an organic polymer layer. The organic polymer layer includes but is not limited to one or more of polyethylene terephthalate (PET), silicone resin, epoxy resin, acrylic resin, phenolic plastic, phenolic resin, amino plastic, urea-formaldehyde resin, hard plastic reaction resin, melamine formaldehyde resin, unsaturated polyester resin, vinyl ester resin, benzene acrylate resin, diallyl phthalate resin, cross-linked polyurethane resin, polymethacrylate reaction resin, polyacrylate reaction resin, acrylic-silicone hybrid, epoxy-silicone hybrid, transparent polyimide, etc.

[0094] The protective layer 203b can be formed by an optically transparent adhesive 206 ( Figure 5 The protective layer 203b may be fixedly connected to the main body layer 203a (not shown) or directly coated on the main body layer 203a. It is understandable that in other embodiments, the cover plate structure 203 may not include the protective layer 203b.

[0095] On this basis, in order to improve the scratch resistance and anti-fingerprint performance of the cover structure 203 , a protective film 300 may be provided on the side of the cover structure 203 away from the display screen 202 . The protective film 300 may be bonded to the cover structure 203 .

[0096] The cover structure 203 in the above embodiment uses ultra-thin glass as the material of the main layer 203a of the cover structure 203, which can reduce the crease in the bending area of ​​the screen 20 (that is, the third display area 23) to a certain extent. However, the mechanical strength of the ultra-thin glass in the related art is still insufficient, resulting in insufficient deformation resistance and recovery ability of the cover structure 203 after deformation. As a result, the screen 20 will still have creases in the bending area of ​​the screen 20 during the folding process. At the same time, the organic materials (such as OCA, organic polymer layer, etc.) in the cover structure 203 are prone to plastic deformation, which is also an important reason why creases are easily formed in the bending area of ​​the screen 20.

[0097] To solve the above technical problems, please refer to Figure 6 , Figure 6 A schematic diagram of the structure of the glass 204 provided for some embodiments of the present application. The glass 204 can be used for the cover structure 203. Exemplarily, the glass 204 can be used for the main layer 203a of the cover structure 203. Specifically, the Young's modulus of the glass 204 is greater than or equal to 90 GPa. Further, the Young's modulus of the glass 204 can be greater than or equal to 100 GPa. Further, the Young's modulus of the glass 204 is greater than or equal to 110 GPa. Exemplarily, the Young's modulus of the glass 204 can be 90 GPa, 91 GPa, 92 GPa, 95 GPa, 98 GPa, 100 GPa, 105 GPa, 108 GPa, 110 GPa, 112 GPa, 115 GPa, 120 GPa, etc. In this way, by setting the Young's modulus of the glass 204 to be greater than or equal to 90 GPa, the rigidity and impact resistance of the glass 204 can be improved, which is beneficial to reducing the deformation of the glass 204, improving the ability of the cover structure 203 to resist deformation and the ability of the cover structure 203 to restore to its original state after deformation, which can reduce the creases in the bending area of ​​the screen 20 and better protect the screen 20.

[0098] Experimental verification shows that when the cover plate structure 203 has the same laminated structure, as the Young's modulus of the glass 204 increases, the crease depth of the bending area thereof will be significantly reduced.

[0099] On this basis, see Figure 6 The glass 204 includes a first surface 204a, a second surface 204b, and a side surface 204c. The first surface 204a and the second surface 204b are located in the thickness direction of the glass 204 (eg Figure 6The side surface 204c is relatively arranged in the direction e) in the figure, and the side surface 204c is connected between the first surface 204a and the second surface 204b. In some embodiments, the first surface 204a faces the display screen 202, and the second surface 204b faces away from the display screen 202. Exemplarily, the first surface 204a can be fixedly connected to the display screen 202 by means of an optically transparent adhesive 206. The second surface 204b can be fixedly connected to the protective layer 203b by means of an optically transparent adhesive 206. Alternatively, the protective layer 203b can be applied to the second surface 204b. Of course, it can be understood that in other embodiments, the second surface 204b can also face the display screen 202, and the first surface 204a can face away from the display screen 202.

[0100] In this embodiment, the surface roughness Ra of the first surface 204a and the second surface 204b is greater than or equal to 3nm and less than or equal to 100nm. That is, the surface roughness Ra of the first surface 204a and the second surface 204b is greater than or equal to 3nm~100nm. Further, the surface roughness value Ra of the first surface 204a and the second surface 204b is greater than or equal to 3nm and less than or equal to 80nm. Further, the surface roughness value Ra of the first surface 204a and the second surface 204b is greater than or equal to 15nm and less than or equal to 80nm. Exemplarily, the surface roughness Ra of the first surface 204a and the second surface 204b can be 3nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, etc. Surface roughness refers to the unevenness of the surface with small spacing and tiny peaks and valleys. The distance (wave distance) between two peaks or two valleys is very small (usually less than 1mm), which belongs to the microscopic geometric shape error. The smaller the surface roughness, the smoother the surface.

[0101] The surface roughness can be measured with reference to GB / T32642-2016 "Measurement Method for Surface Roughness of Flat Panel Display Substrate Glass". Specifically, in this embodiment, the surface roughness can be measured using a stylus surface roughness measuring instrument. The measurement process is: take a piece of the sample to be tested and place it on the platform surface of the stylus surface roughness measuring instrument. The sample to be tested cannot be bent, and the placement time is 5 minutes or longer to ensure that the sample to be tested is consistent with the room temperature; place the test probe on the surface of the sample to be tested, and mark the starting measurement position; press the coordinate adjustment rod to adjust the test probe. When the test probe is completely in contact with the starting measurement of the surface of the sample to be tested, control the test probe to move along the surface of the sample to be tested, measure the actual contour parallel surface, and obtain the true contour shape of the sample to be tested and the corresponding filter curve. Among them, the movement speed of the measuring probe is 0.3mm / min, and the measuring length is 100mm. After the test, read the value of the surface roughness on the stylus surface roughness measuring instrument.

[0102] See also Figure 7a , Figure 7a for Figure 6 The schematic diagram of the structure of the glass 204 at different display ratios is shown. The first surface 204a and the second surface 204b of the glass 204 are both formed with uneven microstructures 204d. Due to the presence of the microstructures 204d, the surface roughness Ra of the first surface 204a and the second surface 204b can be made 3nm~100nm.

[0103] It is understood that the first surface 204a and the second surface 204b of the glass 204 may include a plurality of microstructures 204d, and the shapes of the plurality of microstructures 204d may be the same or different. When the shapes of the plurality of microstructures 204d are the same, refer to Figure 7a The shape of the microstructure 204d may be a prism shape. Of course, the shape of the microstructure 204d may also be other shapes. For example, see Figure 7b , Figure 7b Schematic diagram of microstructure 204d provided in some other embodiments of the present application. Figure 7b As shown in (b1) in FIG. 1 , the shape of the microstructure 204d can also be a hemispherical shape. Figure 7b As shown in (b2) in FIG. 1 , the shape of the microstructure 204d can also be a triangle (also called a pyramid). Figure 7b As shown in (b3) and (b4) in FIG. 1 , the shape of the microstructure 204d may also be an irregular shape.

[0104] When the shapes of the plurality of microstructures 204 d are different, the shapes of the plurality of microstructures 204 d may include, but are not limited to, at least two of a prism shape, a hemisphere shape, a triangle shape, and an irregular shape.

[0105] In some embodiments, the microstructure 204d can be formed in the thinning process mentioned below, or can be formed by other methods such as laser etching, as long as the surface roughness Ra of the first surface 204a and the second surface 204b is guaranteed to be 3nm~100nm.

[0106] See also Figure 8 , Figure 8 For scanning using atomic force microscopy (AFM) Figure 6 The scanned image of the first surface 204a of the glass 204 is obtained. Figure 8 It can be seen that the first surface 204 a of the glass 204 presents an uneven microstructure morphology.

[0107] Thus, by setting the surface roughness Ra of the first surface 204a and the second surface 204b to 3nm~100nm, the contact area between the first surface 204a, the second surface 204b and the organic material (such as the optical transparent glue 206 mentioned above, the organic polymer layer, etc.) can be increased, the adhesion between the first surface 204a, the second surface 204b and the organic material can be improved, and the risk of the organic material attached to the first surface 204a, the second surface 204b peeling off from the first surface 204a, the second surface 204b can be reduced or even avoided, so that the deformation of the organic material during the folding process can be slowed down, and the creases of the cover plate structure 203 and the screen 20 can be reduced. In addition, by setting the surface roughness Ra of the first surface 204a and the second surface 204b to 3nm~100nm, the haze of the glass 204 can be reduced, the transmittance of the glass 204 can be improved, the optical performance of the glass 204 can be guaranteed, and the optical performance of the cover plate structure can be guaranteed.

[0108] It is understandable that in other embodiments, the surface roughness Ra of only one of the first surface 204a and the second surface 204b may be set to 3nm~100nm. In this way, the deformation of the organic material during the folding process can be slowed down to a certain extent, thereby reducing the creases of the cover structure 203 and the screen 20, and ensuring the optical performance of the glass 204.

[0109] Therefore, the glass 204 in the embodiment of the present application has a beneficial effect on resisting the generation of creases and recovering from creases by setting the Young's modulus of the glass 204 to be greater than or equal to 90 GPa and setting the surface roughness Ra of at least one of the first surface 204a and the second surface 204b of the glass 204 to 3nm~100nm. When the glass 204 is applied to the cover structure 203 of the screen 20, the creases in the bending area of ​​the screen 20 can be effectively reduced, thereby improving the display aesthetics of the screen 20.

[0110] Please continue reading Figure 6 In some embodiments, the side surface 204c of the glass 204 is formed as a curved surface. Specifically, the side surface 204c of the glass 204 is formed as a circular arc surface. Exemplarily, the central angle of the circular arc surface is 180 degrees, that is, the circular arc surface is a semicircular arc surface. It can be understood that in other embodiments, the side surface 204c of the glass 204 can also be formed as an elliptical curved surface, a semi-curved surface, etc. In addition, the shape of the side surface 204c of the glass 204 in the embodiment of the present application can be combined with the glass 204 in any of the above embodiments.

[0111] In some embodiments, the edge of the glass 204 may be chemically etched to form a curved surface on the side surface 204c of the glass 204. In other embodiments, the curved surface may also be formed by the surface tension of the glass 204 itself during the heat treatment of the glass 204.

[0112] The glass 204 in this embodiment can reduce stress at the edge of the glass 204 by setting the side surface 204c of the glass 204 to a curved surface, which is beneficial to improving the bending strength of the glass 204, thereby helping to further reduce the creases in the bending area of ​​the screen 20.

[0113] In some embodiments, the thickness of the glass 204 is greater than or equal to 0.02 mm and less than or equal to 0.1 mm. That is, the thickness of the glass 204 is 0.020 mm to 0.100 mm. The glass 204 is ultra-thin glass. Further, the thickness of the glass 204 is greater than or equal to 0.02 mm and less than or equal to 0.05 mm. Exemplarily, the thickness of the glass 204 can be 0.02 mm, 0.03 mm, 0.04 mm, 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm, 0.1 mm, etc. In this way, the bending performance and mechanical strength of the glass 204 can be taken into account.

[0114] In some embodiments, glass 204 is microcrystalline glass. That is, the material of glass 204 in the embodiments of the present application is microcrystalline glass. Microcrystalline glass refers to a basic glass of a specific composition with a nucleating agent (or without a nucleating agent), which is subjected to a crystallization heat treatment under a certain temperature system, and a large number of tiny crystals are uniformly precipitated in the glass to form a dense multiphase complex of microcrystalline phase and glass phase. Microcrystalline glass, like ceramics, is composed of crystals, and its atomic arrangement is regular. Therefore, microcrystalline glass has a higher Young's modulus and stronger mechanical strength. In this way, the use of microcrystalline glass to process glass 204 can ensure that glass 204 has a higher Young's modulus, which is conducive to further improving the rigidity of glass 204, thereby further improving the ability of glass 204 and cover plate structure 203 to resist deformation and the ability of glass 204 and cover plate structure 203 to return to their original state after deformation, thereby reducing the creases in the bending area of ​​​​screen 20.

[0115] In order to ensure the optical properties of glass-ceramics while ensuring the mechanical properties of glass-ceramics, reduce the difficulty of processing glass-ceramics, and further ensure the mechanical and optical properties of glass 204, in some embodiments, the main crystalline phase of glass-ceramics includes one or more of spodumene, petalite, lithium silicate, lithium disilicate, β-quartz, zirconium oxide, spinel, and zinc spinel. Among them, the main crystalline phase of glass-ceramics refers to a crystalline phase that has a significant effect on the performance of glass-ceramics. In the glass X-ray diffraction spectrum (XRD), the peak shape of the main crystalline phase is more obvious. The main crystalline phase may contain one or more types. Exemplarily, the type of main crystalline phase is one or two.

[0116] In some embodiments, the mass fraction of the main crystalline phase is greater than or equal to 50%, and further, the mass fraction of the main crystalline phase is greater than or equal to 70%. The mass fraction of the main crystalline phase is equal to the mass of the main crystalline phase divided by the sum of the masses of all crystalline phases in the microcrystalline glass (also referred to as the mass of the total crystalline phase). Exemplarily, the mass fraction of the main crystalline phase can be 50%, 55%, 60%, 65%, 70%, 75%, 78%, 80%, 82%, 83%, 85%, etc. In this way, by controlling the mass fraction of the main crystalline phase to be not less than 50%, the purity of the main crystalline phase can be improved, and the number of scatterings between different crystalline phases can be reduced, thereby improving the transmittance of the microcrystalline glass, reducing the haze of the microcrystalline glass, and improving the optical properties of the microcrystalline glass, which is beneficial to improving the optical properties of the glass 204, the cover structure 203 and the screen 20.

[0117] For example, in some embodiments, the main crystalline phase of the microcrystalline glass is lithium disilicate, and the secondary crystalline phase includes at least one of petalite, lithium metasilicate, zirconium salt, and phosphate crystals. The "secondary crystalline phase" described in this application refers to other crystalline phases except the main crystalline phase.

[0118] In some embodiments, the average particle size of the crystal phase of the microcrystalline glass (that is, the average grain size) is less than or equal to 80 nm. Exemplarily, the average particle size of the crystal phase of the microcrystalline glass is less than or equal to 60 nm. Or the average particle size of the crystal phase of the microcrystalline glass is less than or equal to 40 nm. Or the average particle size of the crystal phase of the microcrystalline glass is less than or equal to 30 nm. The above-mentioned average particle size of the crystal phase of the microcrystalline glass is small, which can ensure that the average transmittance of the microcrystalline glass is high and the haze is small, so that the microcrystalline glass has excellent optical properties, thereby ensuring the optical properties of the glass 204 and the cover structure 203.

[0119] The average crystal grain size is the average value of the crystal grain sizes, which can be measured using a scanning electron microscope (SEM) or an X-ray diffraction (XRD) spectrometer.

[0120] Furthermore, the average particle size of the crystal phase of the microcrystalline glass is greater than or equal to 5nm. Exemplarily, the average particle size of the crystal phase of the microcrystalline glass is 5nm~80nm, or the average particle size of the crystal phase of the microcrystalline glass is 5nm~70nm, or the average particle size of the crystal phase of the microcrystalline glass is 5nm~60nm, or the average particle size of the crystal phase of the microcrystalline glass is 5nm~40nm, or the average particle size of the crystal phase of the microcrystalline glass is 5nm~30nm. If the average particle size of the crystal phase of the microcrystalline glass is too small, it will affect the impact resistance of the microcrystalline glass. Therefore, by controlling the average particle size of the crystal phase of the microcrystalline glass to not less than 5nm, the optical properties and impact resistance of the microcrystalline glass can be taken into account.

[0121] In order to further improve the mechanical properties of the glass 204 and improve the hardness and deformation resistance of the glass 204, in some embodiments, refer to Figure 6 , an ion exchange layer 204e is formed on the surface of the glass 204. The ion exchange layer 204e is indicated by a shaded portion on the surface of the third glass 204C. The ion exchange layer 204e can be formed by chemically strengthening the glass 204. By forming the ion exchange layer 204e on the surface of the glass 204, further expansion of cracks in the glass can be effectively eliminated or suppressed, thereby greatly improving the ability of the glass 204 to resist external forces, and significantly improving the strength of the glass 204.

[0122] Among them, chemical strengthening (also called ion exchange) is commonly referred to as chemical toughening. The main principle of chemical strengthening is to exchange ions with larger radius (such as K ions) in the molten salt with ions with smaller radius (such as Na ions) in the glass, and form a layer of compressive stress on the glass surface through the "crowding effect", and form an ion exchange layer 204e (also called a compressive stress layer) with a certain depth. In the actual processing process, the glass 204 can be chemically strengthened once, or twice.

[0123] Glass fracture is generally caused by the tensile stress on the crack exceeding its tolerance range. When subjected to external force, the crack on the surface of the glass not only extends to the surroundings, but also expands into the interior of the glass. The stress on the crack tip is determined by the following formula σ r =2σ0(a / r) 1 / 2 , where a is the surface crack depth and σ0 is the tensile stress applied longitudinally; when the crack tip extends forward, the stress at a distance r in the extension direction is σr. It can be seen that the stress at the crack tip is much greater than σ0. For a given glass sample, if the distance r and stress σ that play a decisive role in fracture r If is fixed, then σ0(a / r) 1 / 2 It is also a constant, which means that the tensile stress σ0 that the glass can withstand when it breaks is inversely proportional to the square root of the crack depth a. In other words, if the depth of the crack extending into the glass can be effectively controlled (i.e., a is reduced), the tensile stress σ0 that the glass can withstand will increase accordingly, that is, the mechanical strength of the glass will increase accordingly.

[0124] By chemically strengthening the glass 204, on the one hand, a certain compressive stress can be obtained on the surface of the glass 204. When the glass 204 is subjected to external force, the compressive stress on its surface needs to be offset first, and then the glass 204 is put into a tension state. On the other hand, after the glass 204 is chemically strengthened, the ion exchange layer 204e formed on the surface of the glass 204 can effectively eliminate or inhibit the expansion of cracks. Therefore, by chemically strengthening the glass 204, the ability of the glass 204 to resist external forces can be improved, and the strength of the glass 204 can be significantly enhanced.

[0125] In some embodiments, the ion exchange layer 204e includes a K ion exchange layer, and the depth of the K ion exchange layer is 0.06t~0.2t. Wherein, t is the thickness of the glass 204. Exemplarily, when the thickness of the glass 204 is 0.03mm, the depth of the K ion exchange layer 204e is 1.8μm~6μm. Further, the depth of the K ion exchange layer is 0.07t~0.15t. In this case, when the thickness of the glass 204 is 0.03mm, the depth of the K ion exchange layer is 2.1μm~4.5μm. In this way, the mechanical strength, hardness and deformation resistance of the microcrystalline glass can be improved while reducing the processing difficulty of the glass 204.

[0126] Specifically, the glass 204 in the embodiment of the present application contains Na element, so that the glass 204 can undergo K→Na ion exchange during the chemical strengthening process, so that the Na ions in the glass 204 can be replaced by K ions in the molten salt to form a K ion exchange layer 204e.

[0127] On the basis of any of the above embodiments, the ion exchange layer 204e further includes a Na ion exchange layer, and the depth of the Na ion exchange layer is 0.1t~0.25t. Exemplarily, when the thickness of the glass 204 is 0.03mm, the depth of the Na ion exchange layer is 4.5μm~7.5μm. Further, the depth of the Na ion exchange layer is 0.15t~0.2t. That is, the depth of the Na ion exchange layer is 4.5μm~6μm, where t is the thickness of the glass 204. In this way, the mechanical strength, hardness and deformation resistance of the glass 204 can be further improved.

[0128] Specifically, the glass 204 in the embodiment of the present application contains the Li element, so that the glass 204 can undergo Na→Li ion exchange during the chemical strengthening process, so that the Li ions in the glass 204 can be replaced by Na ions in the molten salt to form a Na ion exchange layer.

[0129] It is understandable that the ion exchange layer 204e in the glass 204 may include only one of the K ion exchange layer and the Na ion exchange layer, or may include both the K ion exchange layer and the Na ion exchange layer.

[0130] Specifically, when the ion exchange layer 204e in the glass 204 includes only one of the K ion exchange layer and the Na ion exchange layer, the ion exchange layer 204e can be formed when the glass 204 is subjected to a single chemical strengthening treatment. When the ion exchange layer 204e in the glass 204 includes the K ion exchange layer and the Na ion exchange layer, the ion exchange layer 204e can be formed when the glass 204 is subjected to two chemical strengthening treatments. Exemplarily, when the glass 204 is subjected to the first chemical strengthening treatment, most of the Li ions in the glass 204 can be exchanged with alkali metal ions having a larger ionic radius in the molten salt. When the second chemical strengthening treatment is performed, most of the Na ions in the glass 204 can be exchanged with alkali metal ions having a larger ionic radius in the molten salt. Through two-step ion exchange, the thickness and surface compressive stress value of the ion exchange layer 204e in the glass 204 can be effectively increased.

[0131] The depth of the ion exchange layer 204e can be tested by analyzing the element content of the side 204c of the glass 204 using electron probe microanalysis (EPMA) or scanning electron microscope energy dispersive spectrometer (SEM-EDS). The process of using scanning electron microscope energy dispersive spectrometer (SEM-EDS) to test the depth of the ion exchange layer is as follows: the sample to be tested is cut into small pieces, and the length of one side of the small piece is less than 5mm, and the edge is flat. After a layer of gold film is evaporated on the surface of the small piece sample using a vacuum coating device, the small piece sample is placed on the sample stage of the SEM-EDS for testing. During the test, the position of the small piece sample is adjusted so that the flat edge of the small piece sample appears in the field of view. The SEM / EDS line scanning analysis function is used to scan a straight line perpendicular to the plane of the small piece sample, and then the element composition and content changes on this line are analyzed, and finally the depth of the ion exchange layer is obtained.

[0132] In some embodiments, the glass 204 has good optical properties, and the transmittance of the glass 204 at a wavelength of 550 nm is greater than or equal to 89%. For example, the transmittance of the glass 204 at a wavelength of 550 nm is 89%, 90%, 91%, 92%, etc. In this way, it can be ensured that the glass 204 and the cover structure 203 have excellent optical properties.

[0133] In some embodiments, the pen drop height of the glass 204 is greater than or equal to 20 mm. Further, the pen drop height of the glass 204 is greater than or equal to 25 mm. Further, the pen drop height of the glass 204 is greater than or equal to 30 mm. Exemplarily, the pen drop height of the glass 204 is 20 mm, 21 mm, 22 mm, 23 mm, 24 mm, 25 mm, 26 mm, 27 mm, 28 mm, 29 mm, 30 mm, 31 mm, 32 mm, 35 mm, etc. In this way, the mechanical strength and impact resistance of the glass 204 and the cover plate structure 203 can be improved.

[0134] The test method of pen drop height in this application is: fix the glass to be tested parallel to the steel plate, drop the tip of a signature pen (weight 12g, tip diameter φ0.5mm, Morning Maker) freely with the tip facing and perpendicular to the glass to be tested, and record the maximum height of the tip of the pen from the glass to be tested when the glass to be tested is not damaged or cracked. This maximum height is the pen drop height. This height value can reflect the mechanical strength and impact resistance of the glass.

[0135] On the basis of any of the above embodiments, the glass 204 in this embodiment also has good static bending performance. Specifically, the static limit bending diameter D of the glass 204 is less than or equal to (0.8Et+t) mm. Wherein, E is the Young's modulus of the glass 204, the unit is GPa, and t is the thickness of the glass 204, the unit is mm. When calculating the static limit bending diameter D of the glass 204, E and t in the calculation formula only take numerical values, and the unit is not taken into account. Further, the static limit bending diameter D of the glass 204 is less than or equal to (0.5Et +t) mm. Furthermore, the static limit bending diameter D of the glass 204 is less than or equal to (0.3Et +t) mm. In this way, the bending strength of the glass 204 can be ensured, which is conducive to reducing the creases in the bending area of ​​the glass 204 and the cover structure 203 including the glass 204 and the screen 20.

[0136] For example, in some embodiments, the Young's modulus E of the glass 204 is 90 GPa, and the thickness t of the glass 204 is 0.03 mm. In this case, the value of 0.8Et+t is 0.8*90*0.03+0.03=2.19 mm, so that the static limit bending diameter D of the glass 204 is less than or equal to 2.19 mm.

[0137] Among them, the test method for static bending performance is: use a bending machine to perform inward and outward bending tests on the glass to be tested, bend the glass to be tested to a fixed position and then let it stand for 24 hours, observe whether the glass to be tested has cracks and whitening, and record the maximum bending diameter of the glass to be tested without cracks and whitening. The maximum bending diameter is the static limit bending diameter.

[0138] See also Fig. 9 , Fig. 9 Schematic diagram of glass 204 in a bent state provided in some embodiments of the present application. Glass 204 includes a first portion 2041, a second portion 2042, and a third portion 2043 connected between the first portion 2041 and the second portion 2042. In the bent state, the first portion 2041 and the second portion 2042 of the glass 204 are arranged parallel and opposite to each other, and the third portion 2043 is in a bent state. The bending diameter of the glass 204 described in the embodiments of the present application refers to the diameter of the third portion 2043 of the glass 204 in the bent state.

[0139] In some embodiments, the glass 204 also has good dynamic bending performance. Specifically, the glass 204 can be dynamically bent greater than or equal to 200,000 times when the bending diameter D is (Et + t) mm. That is, the glass to be tested is subjected to inward bending and outward bending tests using a bending machine. At a bending radius of (Et + t) mm, after a cumulative bending number of 200,000 times, no cracks or whitening occurs in the glass to be tested. Wherein, E is the Young's modulus of the glass 204, in GPa, and t is the thickness of the glass 204, in mm. When calculating the bending diameter D of the glass 204, E and t in the calculation formula only take numerical values, and do not take units into account. In this way, the dynamic bending performance of the glass 204 can be guaranteed, and the service life of the glass 204 and the cover structure 203 and screen 20 including the glass 204 can be extended.

[0140] For example, in some embodiments, the Young's modulus E of the glass 204 is 90 GPa, and the thickness t of the glass 204 is 0.03 mm. In this case, the value of Et+t is 90*0.03+0.03=2.73 mm, so that the glass 204 can be dynamically bent greater than or equal to 200,000 times at a bending diameter D of 2.73 mm.

[0141] Furthermore, the glass 204 can be dynamically bent for more than or equal to 300,000 times when the bending diameter D is (Et + t) mm. That is, the glass 204 to be tested is subjected to inward bending and outward bending tests using a bending machine. When the bending radius is (Et + t) mm, after a cumulative bending number of 300,000 times, the glass to be tested does not show cracks or whitening. Thus, the dynamic bending performance of the glass 204 can be further guaranteed, and the service life of the cover plate structure 203 can be extended.

[0142] The following describes a method for preparing the glass 204 in an embodiment of the present application.

[0143] See also Fig.10 , Fig.10 A flow chart of a method for preparing glass provided in some embodiments of the present application. The method for preparing glass comprises:

[0144] Step S100: providing a glass substrate 205, wherein the Young's modulus of the glass substrate 205 is greater than or equal to 90 GPa;

[0145] See also Fig.10 The glass substrate 205 is in a flat plate shape and includes a first surface 205a and a second surface 205b opposite to each other in the thickness direction thereof. Both the first surface 205a and the second surface 205b can be smooth planes.

[0146] In some embodiments, the glass substrate 205 is a microcrystalline glass, which can be the microcrystalline glass in any of the above embodiments. It is understood that in other embodiments, the glass substrate 205 can also be a base glass, as long as the Young's modulus of the glass substrate 205 is greater than or equal to 90 GPa.

[0147] Please continue reading Fig.10 The method for preparing glass further includes: step S200: thinning the glass substrate 205 to a target thickness to obtain a first glass 204A, wherein the first glass 204A includes a first surface 204a and a second surface 204b arranged opposite to each other in the thickness direction thereof, and the surface roughness Ra of the first surface 204a and / or the second surface 204b is greater than or equal to 3nm and less than or equal to 100nm. In some embodiments, the target thickness may be 0.02mm to 0.1mm.

[0148] The first glass 204A is the glass 204 prepared by the preparation method in the embodiment of the present application.

[0149] In some embodiments, the method of thinning the glass substrate 205 includes one or more of chemical thinning, mechanical grinding and polishing, and chemical mechanical polishing.

[0150] In some embodiments, chemical thinning may be used to thin the glass substrate 205. Specifically, thinning the glass substrate 205 includes: chemically thinning the glass substrate 205 to thin the glass substrate 205 to a target thickness to obtain a first glass 204A, and making the surface roughness Ra of the first surface 204a and / or the second surface 204b of the first glass 204A greater than or equal to 3nm and less than or equal to 100nm.

[0151] Among them, chemical thinning is a thinning method that uses an etching solution (also called a corrosive solution) to corrode the surface of the glass substrate 205, so that the surface of the glass substrate 205 is peeled off and the purpose of thinning is achieved. The principle of chemical thinning is: the etching solution reacts with SiO2 in the glass, and SiO2 is the main component of the glass skeleton (also called the glass network structure). After SiO2 reacts with the etching solution, the glass skeleton of the glass is destroyed, resulting in the disintegration of the glass skeleton. After the glass skeleton is disintegrated, some components in the glass (such as Si, Al, alkali metals, alkaline earth metals, nano-microcrystalline particles, etc.) react with the etching solution to form some complexes that dissolve in the etching solution. Another part of the components in the glass (such as nano-microcrystalline particles) directly adheres to the glass surface in the form of precipitation as the glass skeleton disintegrates. The precipitation attached to the glass surface forms the microstructure 204d morphology of the glass surface, which can play a role in adjusting the surface roughness of the glass.

[0152] Specifically, the amount of particles attached to the glass surface can be adjusted by adjusting the components of the etching solution, thereby controlling the surface roughness of the thinned glass substrate 205 and further controlling the surface roughness of the manufactured glass 204 .

[0153] When the glass substrate 205 is subjected to chemical thinning treatment, the glass substrate 205 may be fixed by a fixture, and then an etching liquid may be sprayed on the surface to be thinned of the glass substrate 205, or the surface to be thinned of the glass substrate 205 may be immersed in the etching liquid, so that the surface of the glass substrate 205 is peeled off, thereby achieving the purpose of thinning. The surface to be thinned is the first surface 205a and / or the second surface 205b of the glass substrate 205.

[0154] When the glass substrate 205 is subjected to chemical thinning treatment, the glass substrate 205 may be subjected to double-sided chemical thinning treatment to make the thickness of the glass substrate 205 reach the target thickness, or the glass substrate 205 may be subjected to single-sided chemical thinning treatment to make the thickness of the glass substrate 205 reach the target thickness. Specifically, when the glass substrate 205 is subjected to double-sided chemical thinning treatment, the first surface 205a and the second surface 205b of the glass substrate 205 may be respectively etched by an etching solution to make the thickness of the glass substrate 205 reach the target thickness. In this case, the first surface 205a and the second surface 205b are both surfaces to be thinned.

[0155] When the glass substrate 205 is subjected to a single-sided chemical thinning treatment, the etching solution can be used to etch only one of the first surface 205a and the second surface 205b of the glass substrate 205, so that the thickness of the glass substrate 205 reaches the target thickness. In this case, one of the first surface 205a and the second surface 205b is to be thinned.

[0156] In some embodiments, the etching solution is an acid solution including at least one of hydrofluoric acid, sulfuric acid, phosphoric acid, nitric acid, hydrochloric acid, perchloric acid, carboxylic acid (R-COOH), sulfonic acid (R-SO3H), sulfinic acid (R-SOOH), and thiocarboxylic acid (R-SH). Exemplarily, the etching solution can be a mixed acid solution including hydrofluoric acid, hydrochloric acid, and sulfuric acid. In other embodiments, the etching solution can also be an alkaline solution including NaOH and KOH. Exemplarily, the etching solution can be a mixed alkaline solution including NaOH and KOH.

[0157] In this way, by chemically thinning the glass substrate 205, on the one hand, the purpose of thinning the glass substrate 205 can be achieved, and the glass substrate 205 can be thinned to a target thickness; on the other hand, the surface roughness of the thinned glass substrate 205 can be controlled, and then the surface roughness of the prepared glass 204 can be controlled, so that the surface roughness of at least one of the first surface 204a and the second surface 204b of the prepared glass 204 reaches 3nm~100nm; on the other hand, during the chemical thinning process, the surface to be thinned of the glass substrate 205 is corroded by the etching solution and peeled off, which is conducive to repairing the surface cracks of the glass substrate 205, and then it is conducive to improving the mechanical strength of the prepared glass 204.

[0158] In other embodiments, mechanical grinding and polishing and chemical thinning may be used to thin the glass substrate 205. Specifically, the thinning process for the glass substrate 205 may include:

[0159] Step S201a: mechanically grinding and polishing the glass substrate 205 to thin the glass substrate 205 to a first thickness; the first thickness is less than the target thickness.

[0160] Step S202a: chemically thinning the glass substrate 205 thinned to the first thickness to obtain a first glass 204A, wherein the surface roughness Ra of the first surface 204a and / or the second surface 204b of the first glass 204A is greater than or equal to 3nm and less than or equal to 100nm.

[0161] Among them, mechanical grinding and polishing can achieve the purpose of glass thinning by utilizing the friction between the glass substrate 205 and the grinding powder. In this way, before chemically thinning the glass substrate 205, the glass substrate 205 is firstly subjected to mechanical grinding and polishing, and after the glass substrate 205 is thinned to a certain thickness, the glass substrate 205 is then subjected to chemical thinning, which can improve the thinning efficiency and reduce the thickness tolerance of the prepared glass 204.

[0162] In some other embodiments, thinning the glass substrate 205 may include:

[0163] Step S201b: performing mechanical grinding and polishing on the glass substrate 205 to thin the glass substrate 205 to a first thickness;

[0164] Step S202b: Perform chemical mechanical polishing on the glass substrate 205 thinned to the first thickness to thin the glass substrate 205 to a target thickness to obtain a first glass 204A, wherein the surface roughness Ra of the first surface 204a and / or the second surface 204b of the first glass 204A is greater than or equal to 3nm and less than or equal to 100nm.

[0165] Among them, chemical mechanical polishing is to make the glass to be polished rotate relative to a polishing pad under a certain downward pressure and in the presence of a polishing liquid (a mixture of ultrafine particles, chemical oxidants and liquid media), and use the mechanical grinding of abrasive particles and the corrosion of chemical oxidants to remove materials from the glass surface to achieve the purpose of thinning. The surface roughness of the thinned glass substrate can be adjusted by adjusting the chemical polishing pressure and the composition of the polishing liquid.

[0166] It is understandable that in other embodiments, only one of the thinning methods, mechanical grinding and polishing or chemical mechanical polishing, can be used to thin the glass substrate 205 to the target thickness. Alternatively, a combination of mechanical grinding and polishing, chemical thinning, and chemical mechanical polishing can be used to thin the glass substrate 205 to the target thickness.

[0167] In the method for preparing the glass 204 in the embodiment of the present application, by setting the Young's modulus of the glass substrate 205 to be greater than or equal to 90 GPa, and controlling the surface roughness Ra of the first surface 204a and / or the second surface 204b of the glass 204 (for example, the first glass 204A) obtained after the thinning process to be greater than or equal to 3 nm and less than or equal to 100 nm, on the one hand, the rigidity and impact resistance of the prepared glass 204 can be improved, which is conducive to reducing the deformation of the glass 204, and improving the ability of the cover structure 203 including the glass 204 to resist deformation and the cover structure 203 to resist deformation. The ability to return to its original shape after deformation can reduce the creases in the bending area of ​​the screen 20 and better protect the screen 20. On the other hand, while ensuring the optical properties of the glass 204, the adhesion between the surface of the glass 204 (that is, the first surface 204a and the second surface 204b mentioned above) and the organic material can be increased, reducing or even avoiding the risk of the organic material attached to the surface of the glass 204 being peeled off from the glass 204, thereby slowing down the deformation of the organic material during the folding process, and further reducing the creases of the cover structure 203 and the screen 20. The preparation method is simple and easy to implement.

[0168] In other embodiments, see Fig.11 , Fig.11 Flow chart of a method for preparing glass 204 provided in some other embodiments of the present application. Fig.10 The difference between the preparation method shown is that, in the preparation method of this embodiment, after the glass substrate 205 is thinned to a target thickness to obtain the first glass 204A, the method further includes:

[0169] Step S300: performing edge processing on the first glass 204A so that the side surface 204c of the first glass 204A is formed into a curved surface.

[0170] For example, see Fig.11 , the side surface 204c of the first glass 204A is a surface connected between the first surface 204a and the second surface 204b. After edge processing of the first glass 204A, the side surface 204c of the first glass 204A can be formed into a circular arc surface, an elliptical arc surface, etc., and then the second glass 204B can be obtained. The second glass 204B is the glass 204 prepared by the preparation method in this embodiment.

[0171] Exemplarily, the arc surface is a semi-arc surface. It is understandable that in other embodiments, the arc surface can also be a semi-arc surface. In this way, the side surface 204c of the glass 204 prepared by the preparation method can be formed into an arc surface, which can reduce the edge stress of the glass 204, which is conducive to improving the bending strength of the glass 204, thereby helping to further reduce the crease in the bending area of ​​the screen 20.

[0172] Specifically, in some embodiments, edge treatment of the first glass 204A includes: chemically etching the edge of the first glass 204A. In other embodiments, edge treatment of the first glass 204A may also include: heat treatment of the first glass 204A. During the heat treatment, the side surface 204c of the first glass 204A may be formed into a curved surface by its own surface tension.

[0173] In some other embodiments, see Fig.12 , Fig.12 Flow chart of a method for preparing glass 204 provided in some embodiments of the present application. Fig.11 The difference between the preparation method in the illustrated embodiment is that, in the preparation method in this embodiment, after the glass substrate 205 is thinned to a target thickness to obtain the first glass 204A, the method further comprises:

[0174] Step S400: performing chemical strengthening treatment on the first glass 204A.

[0175] See also Fig.12In this embodiment, after edge treatment is performed on the first glass 204A, the first glass 204A may be subjected to chemical strengthening treatment. Specifically, after edge treatment is performed on the first glass 204A, the second glass 204B is obtained, and the obtained second glass 204B is subjected to chemical strengthening treatment to obtain the third glass 204C. The third glass 204C is the glass 204 obtained by the preparation method of this embodiment. Specifically, an ion exchange layer 204e is formed on the surface of the third glass 204C.

[0176] The ion exchange layer 204e may include a Na ion exchange layer or a K ion exchange layer, or the ion exchange layer 204e may include a K ion exchange layer and a Na ion exchange layer. In this way, the ion exchange layer 204e on the side surface 204c of the first glass 204A can be prevented from being corroded during the edge processing process, thereby ensuring that the ion exchange layer 204e can be formed on the entire surface of the prepared glass 204.

[0177] When the glass substrate 205 is microcrystalline glass, chemically strengthened microcrystalline glass can be obtained after chemical strengthening treatment. When the glass substrate 205 is base glass, chemically strengthened glass can be obtained after chemical strengthening treatment.

[0178] In some embodiments, when the second glass 204B is subjected to chemical strengthening treatment, chemical strengthening may be performed once or twice.

[0179] The preparation method in this embodiment, by chemically strengthening the first glass 204A, can, on the one hand, make the surface of the prepared glass 204 obtain a certain compressive stress. When the glass 204 is subjected to external force, the compressive stress on its surface needs to be offset first, and then the glass 204 is put into a tension state, thereby improving the ability of the glass 204 to resist external force, and the strength of the glass 204 is significantly improved, thereby significantly improving the ability of the glass 204 to resist deformation and the ability to recover to its original state after deformation, thereby reducing the creases in the bending area of ​​the screen 20 and better protecting the screen 20; on the other hand, after the first glass 204A is chemically strengthened, an ion exchange layer 204e of a certain depth will be formed on the surface of the prepared glass 204, so that even if an external force forms a crack on the surface of the glass 204, the formed ion exchange layer 204e will effectively eliminate or inhibit the further expansion of the crack, thereby greatly improving the ability of the glass to resist external force and significantly enhancing the strength of the prepared glass 204.

[0180] It is understandable that step S400 in the embodiment of the present application can be combined with the preparation method in any embodiment of the present application. Exemplarily, when the preparation method does not include step S300, the first glass 204A can be directly subjected to chemical strengthening treatment.

[0181] In some other embodiments, see Fig.13 , Fig.13 Flow chart of a method for preparing glass 204 provided in some embodiments of the present application. Fig.12 The difference between the preparation method in the illustrated embodiment is that, in the preparation method in this embodiment, after the glass substrate 205 is thinned to a target thickness to obtain the first glass 204A, the method further comprises:

[0182] Step S500: Chemical polishing is performed on the first glass 204A. Chemical polishing refers to a method of further dissolving the uneven areas on the glass surface by chemical etching with chemical reagents to passivate the wear marks and etch and level the surface. In this way, the surface uniformity of the prepared glass 204 can be improved, which is conducive to further improving the mechanical strength of the glass 204.

[0183] Specifically, in this embodiment, the first glass 204A can be edge-processed to obtain the second glass 204B, and then the obtained second glass 204B is chemically strengthened to obtain the third glass 204C, and then the third glass 204C is chemically polished to obtain the fourth glass 204D. The fourth glass 204D is the glass 204 obtained by the preparation method of this embodiment. In this way, the surface uniformity of the obtained glass 204 can be further guaranteed.

[0184] It can be understood that step S500 in the embodiment of the present application can be combined with the preparation method in any embodiment of the present application.

[0185] The preparation method of the glass 204 in the present application is described in detail below in conjunction with specific embodiments.

[0186] Example 1

[0187] The method for preparing the glass 204 in the embodiment of the present application includes:

[0188] The preparation method of glass 204 includes:

[0189] (1) providing a glass substrate 205, wherein the glass substrate 205 is microcrystalline glass, and the Young's modulus of the glass substrate 205 is 90 GPa and the thickness is 0.2 mm;

[0190] (2) performing a thinning process on the glass substrate 205: performing a chemical thinning process on the first surface 205a of the glass substrate 205, and performing a chemical thinning process on the second surface 205b of the glass substrate 205, so that the thickness of the glass substrate 205 is thinned to 0.03 mm, and the surface roughness Ra of the first surface 205a of the glass substrate 205 after thinning is 5 nm, and the surface roughness Ra of the second surface 205b of the glass substrate 205 is 5 nm;

[0191] (3) performing edge processing on the thinned glass substrate 205: performing chemical etching on the edge of the glass substrate 205 so that the side surface of the thinned glass substrate 205 is a semicircular arc surface;

[0192] (4) chemically strengthening the glass substrate 205 after edge treatment: the glass substrate 205 is chemically strengthened to form a K ion exchange layer on the surface of the glass substrate 205. The depth of the K ion exchange layer 204e is 4 μm.

[0193] (5) The glass substrate 205 that has been chemically strengthened is subjected to chemical polishing to obtain glass 204 .

[0194] The properties of the glass 204 are shown in Table 1.

[0195] Example 2

[0196] The method for preparing the glass 204 in the embodiment of the present application includes:

[0197] The preparation method of glass 204 includes:

[0198] (1) providing a glass substrate 205, wherein the glass substrate 205 is microcrystalline glass, and the Young's modulus of the glass substrate 205 is 90 GPa and the thickness is 0.2 mm;

[0199] (2) Thinning the glass substrate 205: chemically thinning the first surface 205a of the glass substrate 205 and chemically thinning the second surface 205b of the glass substrate 205, so that the thickness of the glass substrate 205 is thinned to 0.03 mm, and the surface roughness Ra of the first surface 205a of the glass substrate 205 after thinning is 45 nm, and the surface roughness Ra of the second surface 205b is 5 nm;

[0200] (3) performing edge processing on the thinned glass substrate 205: performing chemical etching on the edge of the glass substrate 205 so that the side surface of the thinned glass substrate 205 is a semicircular arc surface;

[0201] (4) chemically strengthening the glass substrate 205 after edge treatment: chemically strengthening the glass substrate 205 to form a K ion exchange layer on the surface of the glass substrate 205, where the depth of the K ion exchange layer is 4 μm;

[0202] (5) The glass substrate 205 that has been chemically strengthened is subjected to chemical polishing to obtain glass 204 .

[0203] The properties of the glass 204 are shown in Table 1.

[0204] Example 3

[0205] The method for preparing the glass 204 in the embodiment of the present application includes:

[0206] The preparation method of glass 204 includes:

[0207] (1) providing a glass substrate 205, wherein the glass substrate 205 is microcrystalline glass, and the Young's modulus of the glass substrate 205 is 90 GPa and the thickness is 0.2 mm;

[0208] (2) Thinning the glass substrate 205: chemically thinning the first surface 205a of the glass substrate 205 and chemically thinning the second surface 205b of the glass substrate 205, so that the thickness of the glass substrate 205 is thinned to 0.03 mm, and the surface roughness Ra of the first surface 205a of the glass substrate 205 after thinning is 45 nm, and the surface roughness Ra of the second surface 205b is 40 nm;

[0209] (3) performing edge processing on the thinned glass substrate 205: performing chemical etching on the edge of the glass substrate 205 so that the side surface of the thinned glass substrate 205 is a semicircular arc surface;

[0210] (4) chemically strengthening the glass substrate 205 after edge treatment: chemically strengthening the glass substrate 205 to form a K ion exchange layer on the surface of the glass substrate 205, where the depth of the K ion exchange layer is 4 μm;

[0211] (5) The glass substrate 205 that has been chemically strengthened is subjected to chemical polishing to obtain glass 204 .

[0212] The properties of the glass 204 are shown in Table 1.

[0213] Example 4

[0214] The method for preparing the glass 204 in the embodiment of the present application includes:

[0215] The preparation method of glass 204 includes:

[0216] (1) providing a glass substrate 205, wherein the glass substrate 205 is microcrystalline glass, and the Young's modulus of the glass substrate 205 is 100 GPa and the thickness is 0.2 mm;

[0217] (2) Thinning the glass substrate 205: After mechanical grinding and polishing are performed on the first surface 205a and the second surface 205b of the glass substrate 205, the first surface 205a of the glass substrate 205 is chemically thinned, and the second surface 205b of the glass substrate 205 is chemically thinned, so that the thickness of the glass substrate 205 is thinned to 0.03 mm, and the surface roughness Ra of the first surface 205a of the glass substrate 205 after thinning is 5 nm, and the surface roughness Ra of the second surface 205b is 5 nm;

[0218] (3) performing edge processing on the thinned glass substrate 205: performing chemical etching on the edge of the glass substrate 205 so that the side surface of the thinned glass substrate 205 is a semicircular arc surface;

[0219] (4) chemically strengthening the glass substrate 205 after the edge treatment: the glass substrate 205 is subjected to a first chemical strengthening treatment to form a Na ion exchange layer on the surface of the glass substrate 205, and the depth of the Na ion exchange layer is 7 μm; the glass substrate 205 subjected to the first chemical strengthening treatment is subjected to a second chemical strengthening treatment to form a K ion exchange layer on the surface of the glass substrate 205, and the depth of the K ion exchange layer is 3 μm;

[0220] (5) The glass substrate 205 that has been chemically strengthened is subjected to chemical polishing to obtain glass 204 .

[0221] The properties of the glass 204 are shown in Table 1.

[0222] Example 5

[0223] The method for preparing the glass 204 in the embodiment of the present application includes:

[0224] The preparation method of glass 204 includes:

[0225] (1) providing a glass substrate 205, wherein the glass substrate 205 is microcrystalline glass, and the Young's modulus of the glass substrate 205 is 100 GPa and the thickness is 0.2 mm;

[0226] (2) Thinning the glass substrate 205: After mechanical grinding and polishing are performed on the first surface 205a and the second surface 205b of the glass substrate 205, the first surface 205a of the glass substrate 205 is chemically thinned to reduce the thickness of the glass substrate 205 to 0.03 mm. After the thinning, the surface roughness Ra of the first surface 205a of the glass substrate 205 is 50 nm, and the surface roughness Ra of the second surface 205b is 5 nm.

[0227] (3) performing edge processing on the thinned glass substrate 205: performing chemical etching on the edge of the glass substrate 205 so that the side surface of the thinned glass substrate 205 is a semicircular arc surface;

[0228] (4) chemically strengthening the glass substrate 205 after the edge treatment: the glass substrate 205 is subjected to a first chemical strengthening treatment to form a Na ion exchange layer on the glass substrate 205, and the depth of the Na ion exchange layer is 7 μm; the glass substrate 205 subjected to the first chemical strengthening treatment is subjected to a second chemical strengthening treatment to form a K ion exchange layer on the glass substrate 205, and the depth of the K ion exchange layer is 3 μm;

[0229] (5) The glass substrate 205 that has been chemically strengthened is subjected to chemical polishing to obtain glass 204 .

[0230] The properties of the glass 204 are shown in Table 1.

[0231] Example 6

[0232] The method for preparing the glass 204 in the embodiment of the present application includes:

[0233] The preparation method of glass 204 includes:

[0234] (1) providing a glass substrate 205, wherein the glass substrate 205 is microcrystalline glass, and the Young's modulus of the glass substrate 205 is 100 GPa and the thickness is 0.2 mm;

[0235] (2) Thinning the glass substrate 205: After mechanical grinding and polishing are performed on the first surface 205a and the second surface 205b of the glass substrate 205, the first surface 205a of the glass substrate 205 is chemically thinned, and the second surface 205b of the glass substrate 205 is chemically thinned, so that the thickness of the glass substrate 205 is thinned to 0.03 mm, and the surface roughness Ra of the first surface 205a of the glass substrate 205 after thinning is 35 nm, and the surface roughness Ra of the second surface 205b is 35 nm;

[0236] (3) performing edge processing on the thinned glass substrate 205: performing chemical etching on the edge of the glass substrate 205 so that the side surface of the thinned glass substrate 205 is a semicircular arc surface;

[0237] (4) chemically strengthening the glass substrate 205 after the edge treatment: the glass substrate 205 is subjected to a first chemical strengthening treatment to form a Na ion exchange layer on the glass substrate 205, and the depth of the Na ion exchange layer is 7 μm; the glass substrate 205 subjected to the first chemical strengthening treatment is subjected to a second chemical strengthening treatment to form a K ion exchange layer on the glass substrate 205, and the depth of the K ion exchange layer is 3 μm;

[0238] (5) The glass substrate 205 that has been chemically strengthened is subjected to chemical polishing to obtain glass 204 .

[0239] The properties of the glass 204 are shown in Table 1.

[0240] Example 7

[0241] The method for preparing the glass 204 in the embodiment of the present application includes:

[0242] The preparation method of glass 204 includes:

[0243] (1) providing a glass substrate 205, wherein the glass substrate 205 is microcrystalline glass, and the Young's modulus of the glass substrate 205 is 110 GPa and the thickness is 0.2 mm;

[0244] (2) Thinning the glass substrate 205: After mechanical grinding and polishing are performed on the first surface 205a and the second surface 205b of the glass substrate 205, the first surface 205a of the glass substrate 205 is chemically thinned, and the second surface 205b of the glass substrate 205 is chemically thinned, so that the thickness of the glass substrate 205 is thinned to 0.03 mm, and the surface roughness Ra of the first surface 205a of the glass substrate 205 after thinning is 5 nm, and the surface roughness Ra of the second surface 205b is 5 nm;

[0245] (3) performing edge processing on the thinned glass substrate 205: performing chemical etching on the edge of the glass substrate 205 so that the side surface of the thinned glass substrate 205 is a semicircular arc surface;

[0246] (4) chemically strengthening the glass substrate 205 after the edge treatment: the glass substrate 205 is subjected to a first chemical strengthening treatment to form a Na ion exchange layer on the glass substrate 205, and the depth of the Na ion exchange layer is 8 μm; the glass substrate 205 subjected to the first chemical strengthening treatment is subjected to a second chemical strengthening treatment to form a K ion exchange layer on the glass substrate 205, and the depth of the K ion exchange layer is 2 μm;

[0247] (5) The glass substrate 205 that has been chemically strengthened is subjected to chemical polishing to obtain glass 204 .

[0248] The properties of the glass 204 are shown in Table 1.

[0249] Example 8

[0250] The method for preparing the glass 204 in the embodiment of the present application includes:

[0251] The preparation method of glass 204 includes:

[0252] (1) providing a glass substrate 205, wherein the glass substrate 205 is microcrystalline glass, and the Young's modulus of the glass substrate 205 is 110 GPa and the thickness is 0.2 mm;

[0253] (2) Thinning the glass substrate 205: After mechanical grinding and polishing are performed on the first surface 205a and the second surface 205b of the glass substrate 205, the first surface 205a of the glass substrate 205 is chemically thinned, and the second surface 205b of the glass substrate 205 is chemically thinned, so that the thickness of the glass substrate 205 is thinned to 0.03 mm, and the surface roughness Ra of the first surface 205a of the glass substrate 205 after thinning is 50 nm, and the surface roughness Ra of the second surface 205b is 5 nm;

[0254] (3) performing edge processing on the thinned glass substrate 205: performing chemical etching on the edge of the glass substrate 205 so that the side surface of the thinned glass substrate 205 is a semicircular arc surface;

[0255] (4) chemically strengthening the glass substrate 205 after the edge treatment: the glass substrate 205 is subjected to a first chemical strengthening treatment to form a Na ion exchange layer on the glass substrate 205, and the depth of the Na ion exchange layer is 8 μm; the glass substrate 205 subjected to the first chemical strengthening treatment is subjected to a second chemical strengthening treatment to form a K ion exchange layer on the glass substrate 205, and the depth of the K ion exchange layer is 2 μm;

[0256] (5) The glass substrate 205 that has been chemically strengthened is subjected to chemical polishing to obtain glass 204 .

[0257] The properties of the glass 204 are shown in Table 1.

[0258] Example 9

[0259] The method for preparing the glass 204 in the embodiment of the present application includes:

[0260] The preparation method of glass 204 includes:

[0261] (1) providing a glass substrate 205, wherein the glass substrate 205 is a microcrystalline glass, the Young's modulus of the microcrystalline glass is 110 GPa, and the thickness is 0.2 mm;

[0262] (2) Thinning the glass substrate 205: After mechanically grinding and polishing the first surface 205a and the second surface 205b of the glass substrate 205, the first surface 205a of the glass substrate 205 is subjected to chemical mechanical polishing and thinning, and the second surface 205b of the glass substrate 205 is subjected to chemical mechanical polishing and thinning, so that the thickness of the glass substrate 205 is thinned to 0.03 mm, and the surface roughness Ra of the first surface 205a of the glass substrate 205 after thinning is 3 nm, and the surface roughness Ra of the second surface 205b is 3 nm;

[0263] (3) performing edge processing on the thinned glass substrate 205: performing chemical etching on the edge of the glass substrate 205 so that the side surface of the thinned glass substrate 205 is a semicircular arc surface;

[0264] (4) chemically strengthening the glass substrate 205 after the edge treatment: the glass substrate 205 is subjected to a first chemical strengthening treatment to form a Na ion exchange layer on the glass substrate 205, and the depth of the Na ion exchange layer is 8 μm; the glass substrate 205 subjected to the first chemical strengthening treatment is subjected to a second chemical strengthening treatment to form a K ion exchange layer on the glass substrate 205, and the depth of the K ion exchange layer is 2 μm;

[0265] (5) The glass substrate 205 that has been chemically strengthened is subjected to chemical polishing to obtain glass 204 .

[0266] The properties of the glass 204 are shown in Table 1.

[0267] Comparative Example 1

[0268] The method for preparing the glass 204 in the embodiment of the present application includes:

[0269] The preparation method of glass 204 includes:

[0270] (1) providing a glass substrate 205, wherein the glass substrate 205 is a base glass, and the base glass has a Young's modulus of 73 GPa and a thickness of 0.2 mm;

[0271] (2) Thinning the glass substrate 205: chemically thinning the first surface 205a of the glass substrate 205 and chemically thinning the second surface 205b of the glass substrate 205, so that the thickness of the glass substrate 205 is thinned to 0.03 mm, and the surface roughness Ra of the first surface 205a of the glass substrate 205 after thinning is 5 nm, and the surface roughness Ra of the second surface 205b of the glass substrate 205 is 5 nm;

[0272] (3) performing edge processing on the thinned glass substrate 205: performing chemical etching on the edge of the glass substrate 205 so that the side surface of the thinned glass substrate 205 is a semicircular arc surface;

[0273] (4) chemically strengthening the glass substrate 205 after edge treatment: chemically strengthening the glass substrate 205 to form a K ion exchange layer on the glass substrate 205, where the depth of the K ion exchange layer is 4 μm;

[0274] (5) The glass substrate 205 that has been chemically strengthened is subjected to chemical polishing to obtain glass 204 .

[0275] The properties of the glass 204 are shown in Table 1.

[0276] Table 1 Performance of 3D glass cover plates in Examples 1-9 and Comparative Example 1

[0277] Test items Comparative Example 1 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Thickness (mm) 0.03 0.03 0.03 0.03 0.03 0.03 0.03 0.03 0.03 0.03 Young's modulus (GPa) 73 90 90 90 100 100 100 110 110 110 Transmittance (550nm) 92% 92% 91% 90% 92% 91% 90% 92% 91% 92% Surface roughness Ra of the first surface (nm) 5 5 45 45 5 50 35 5 50 3 Surface roughness of the second surface Ra (nm) 5 5 5 40 5 5 35 5 5 3 K ion exchange layer depth (μm) 4 4 4 4 3 3 3 2 2 2 Na ion exchange layer depth (μm) / / / / 7 7 7 8 8 8 Pen drop height (mm) 9 24 28 29 30 29 32 31 30 29 Peeling force between the organic material attached to the first surface and the first surface (N / cm) 18 18 26 26 19 31 22 18 29 17 Peel force between the organic material attached to the second surface and the second surface (N / cm) 18 18 19 24 19 18 22 18 19 18 Crease depth after screen bending (mm) 0.203 0.142 0.131 0.123 0.109 0.092 0.078 0.094 0.083 0.096

[0278] As can be seen from Table 1, the Young's modulus of the glass 204 in Comparative Example 1 is 73 GPa, the surface roughness Ra of the first surface 204a is 5 nm, and the surface roughness Ra of the second surface 204b is 5 nm, which does not satisfy the Young's modulus greater than or equal to 90 GPa and the surface roughness Ra of at least one of the first surface 204a and the second surface 204b is 3 nm~100 nm.

[0279] The glass 204 in this embodiment has excellent optical properties. Specifically, the transmittance of light at 550nm is 92%. In addition, the first surface 204a and the second surface 204b of the glass 204 have a large peeling force with the organic material. Specifically, the peeling force between the organic material attached to the first surface 204a and the first surface 204a is 18N / cm, and the peeling force between the organic material attached to the second surface 204b and the first surface 204a is 18N / cm. However, the impact resistance of the glass 204 in the pen drop test and the performance of the crease depth test after the screen 20 is bent are not ideal. Specifically, the pen drop height is 9mm, and the crease depth of the screen 20 after bending is 0.203mm.

[0280] The peeling force in the embodiment of the present application can be measured with reference to GB / T 2792-2014 "Test Method for Peel Strength of Adhesive Tape". The test process of peeling force (also known as peeling strength) is as follows: stick the transparent adhesive layer on the target surface of the glass, lift up the transparent adhesive layer and fold it 180 degrees, then pull the transparent adhesive layer at a speed of 300 mm / min to peel it off from the target surface, and measure the pulling force of pulling the transparent adhesive layer during this process. When the peeling distance reaches 70 mm, the average pulling force measured is the peeling force between the transparent adhesive layer and the target surface. The greater the peeling force, the greater the bonding force between the transparent adhesive layer and the target surface.

[0281] The method for testing the crease depth of the screen 20 after bending in the embodiment of the present application is: Fig.14 The screen 20 shown is stacked with the same laminated structure (with a total thickness of about 650 μm), and then the stacked screen samples are fixed on a dynamic bending fixture, and after being bent 30,000 times with a radius R of 1.5 mm, the crease depth of the bending area of ​​the screen sample is measured.

[0282] The Young's modulus of the glass 204 in Examples 1 to 9 is 90 GPa to 110 GPa, the surface roughness Ra of the first surface 204a is 3 nm to 50 nm, and the surface roughness Ra of the first surface 204a is 3 nm to 40 nm, satisfying that the Young's modulus is greater than or equal to 90 GPa and the surface roughness Ra of at least one of the first surface 204a and the second surface 204b is 3 nm to 100 nm.

[0283] The glass 204 in Examples 1 to 9 all have excellent optical properties, specifically: the transmittance at 550nm light is 90% to 92%. In addition, the first surface 204a and the second surface 204b of the glass 204 have a large peeling force with the organic material. The peeling force between the organic material attached to the first surface 204a and the first surface 204a is greater than or equal to 18 N / cm, and the peeling force between the organic material attached to the second surface 204b and the first surface 204a is also greater than or equal to 18 N / cm. Specifically, the peeling force between the organic material attached to the first surface 204a and the first surface 204a is 18N / cm to 31N / cm, and the peeling force between the organic material attached to the second surface 204b and the second surface 204b is 18N / cm to 24 N / cm.

[0284] The glass 204 of Examples 1 to 9 exhibits excellent impact resistance in the pen drop height test, specifically, the pen drop height is 24 mm to 32 mm. In addition, the screen 20 having the glass 204 of Examples 1 to 9 also performs well in the crease depth test, specifically, the crease depth of the screen 20 after bending is 0.078 mm to 0.142 mm.

[0285] Furthermore, by comparing the performance of the glass 204 of Examples 1 to 9 in Table 1, it can be seen that when the glass 204 has the same Young's modulus, as the surface roughness of the glass 204 increases, the crease depth of the bent area of ​​the screen 20 decreases. When the glass 204 has the same surface roughness, as the Young's modulus of the glass 204 increases, the crease depth of the bent area of ​​the screen 20 decreases.

[0286] In summary, in the embodiment of the present application, by setting the Young's modulus of the glass 204 to be greater than or equal to 90 GPa and the surface roughness Ra of at least one of the first surface 204a and the second surface 204b to be 3nm~100nm, the impact resistance of the glass 204 can be improved, the mechanical strength of the glass 204 can be ensured, and the bonding force between the glass 204 and the organic material can be improved, thereby reducing the creases of the screen 20 and the electronic device 100 including the glass 204.

[0287] Specifically, the impact resistance of the glass 204 provided in the embodiment of the present application can be improved by 1.67 to 2.55 times compared with that in comparative example 1, including that the crease depth of the screen 20 of the glass 204 provided in the embodiment of the present application after bending can be reduced by 30% to 61.6% compared with that in comparative example 1.

[0288] In the embodiment of the present application, by applying the above-mentioned glass 204 to the cover structure 203 of the electronic device 100, since the glass 204 has a higher Young's modulus, the rigidity and impact resistance of the cover structure 203 can be improved, which is beneficial to reducing the deformation of the cover structure 203, improving the ability of the cover structure 203 to resist deformation and the ability of the cover structure 203 to restore to its original state after deformation, which can reduce the creases in the bending area of ​​the screen 20 and better protect the screen 20.

[0289] Furthermore, since the surface roughness Ra of the first surface 204a and / or the second surface 204b of the glass 204 is 3nm~100nm, the contact area between the first surface 204a and / or the second surface 204b and the organic material can be increased, thereby enhancing the adhesion between the two, thereby slowing down the deformation of the organic material and achieving the effect of reducing creases, thereby effectively improving the display aesthetics of the electronic device 100.

[0290] Specifically, when the glass 204 is applied to Figure 5When the cover plate structure 203 is shown, the peeling force between the cover plate structure 203 and the display screen 202, and the peeling force between the protective layer 203b in the cover plate structure 203 and the glass 204 can be improved. The peeling force between the cover plate structure 203 and the display screen 202 can be greater than or equal to 18N / cm, and the peeling force between the protective layer 203b and the glass 204 is greater than or equal to 18N / cm. In this way, the bonding force between the cover plate structure 203 and the display screen 202, and the bonding force between the protective layer 203b in the cover plate structure 203 and the glass 204 can be ensured, so as to achieve the effect of reducing the crease of the screen 20, thereby effectively improving the display aesthetics of the electronic device 100.

[0291] It should be noted that when the protective layer 203b is fixedly connected to the glass 204 through the optically transparent adhesive 206, the peeling force between the protective layer 203b and the glass 204 is the peeling force between the optically transparent adhesive 206 and the glass 204. When the protective layer 203b is directly coated on the glass 204, the peeling force between the protective layer 203b and the glass 204 is the peeling force between the protective layer 203b itself and the glass 204.

[0292] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.

[0293] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A glass, characterized in that: The glass includes a first surface and a second surface arranged opposite to each other in a thickness direction thereof, the surface roughness of at least one of the first surface and the second surface is greater than or equal to 15 nm and less than or equal to 100 nm, the Young's modulus of the glass is greater than or equal to 90 GPa, and the thickness of the glass is greater than or equal to 0.02 mm and less than 0.1 mm.

2. The glass according to claim 1, characterized in that A surface roughness of at least one of the first surface and the second surface is less than or equal to 80 nm.

3. The glass according to claim 1, characterized in that The glass is glass-ceramics.

4. The glass according to claim 3, characterized in that The microcrystalline glass includes a main crystal phase, and the main crystal phase is one or more of spodumene, petalite, lithium silicate, lithium disilicate, β-quartz, zirconia, and spinel.

5. The glass according to claim 3, characterized in that The microcrystalline glass includes a main crystalline phase, and the mass fraction of the main crystalline phase is greater than or equal to 50%.

6. The glass according to claim 3, characterized in that The average particle size of the crystal phase of the microcrystalline glass is greater than or equal to 5 nm and less than or equal to 80 nm.

7. The glass according to any one of claims 1 to 6, characterized in that: The thickness of the glass is less than or equal to 0.05 mm.

8. The glass according to any one of claims 1 to 6, characterized in that: The transmittance of the glass at a wavelength of 550 nm is greater than or equal to 89%.

9. The glass according to any one of claims 1 to 6, characterized in that: The pen drop height of the glass is greater than or equal to 20mm.

10. The glass according to any one of claims 1 to 6, characterized in that: The static limit bending diameter of the glass is less than or equal to (0.8Et+t) mm; wherein E is the Young's modulus of the glass, in GPa, and t is the thickness of the glass, in mm.

11. The glass according to any one of claims 1 to 6, characterized in that: The glass is dynamically bent at a bending diameter of (Et + t) mm for a number of times greater than or equal to 200,000 times.

12. The glass according to any one of claims 1 to 6, characterized in that: An ion exchange layer is formed on the surface of the glass.

13. The glass according to claim 12, characterized in that The ion exchange layer includes a K ion exchange layer, and the depth of the K ion exchange layer is greater than or equal to 0.06t and less than or equal to 0.2t, wherein t is the thickness of the glass, in mm.

14. The glass according to claim 12, characterized in that The ion exchange layer includes a Na ion exchange layer, and the depth of the Na ion exchange layer is greater than or equal to 0.15t and less than or equal to 0.25t, wherein t is the thickness of the glass, in mm.

15. The glass according to any one of claims 1 to 6, characterized in that: The glass includes a side surface, the side surface is connected between the first surface and the second surface, and the side surface is a curved surface.

16. A method for preparing glass, characterized in that: include: Providing a glass substrate, wherein the Young's modulus of the glass substrate is greater than or equal to 90 GPa; The glass substrate is thinned to a target thickness to obtain a first glass, wherein the first glass includes a first surface and a second surface opposite to each other in a thickness direction thereof, the surface roughness of the first surface and / or the second surface is greater than or equal to 15 nm and less than or equal to 100 nm, and the thickness of the glass is greater than or equal to 0.02 mm and less than 0.1 mm.

17. The preparation method according to claim 16, characterized in that: The method for thinning the glass substrate includes one or more of chemical thinning, mechanical grinding and polishing, and chemical mechanical polishing.

18. The preparation method according to claim 16, characterized in that: After obtaining the first glass, the preparation method further includes: performing edge processing on the first glass so that the side surface of the first glass is formed into a curved surface.

19. The preparation method according to claim 16, characterized in that: After obtaining the first glass, the preparation method further includes: performing chemical strengthening treatment on the first glass to form an ion exchange layer on the surface of the first glass.

20. The preparation method according to any one of claims 16 to 19, characterized in that: After obtaining the first glass, the preparation method further comprises: performing chemical polishing on the first glass.

21. A cover plate structure, characterized in that: The invention comprises the glass according to any one of claims 1 to 15 or the glass prepared by the preparation method according to any one of claims 16 to 20.

22. The cover plate structure according to claim 21, characterized in that: Also includes: A protective layer is fixedly connected to the first surface or the second surface of the glass.

23. The cover plate structure according to claim 22, characterized in that: The peeling force between the protective layer and the glass is greater than or equal to 18 N / cm.

24. An electronic device, characterized in that: include: A screen, comprising a display screen and a cover plate structure arranged in a stacked manner, wherein the cover plate structure is located on the side to which the display surface of the display screen faces, and the cover plate structure is the cover plate structure described in any one of claims 21-23.

25. The electronic device according to claim 24, characterized in that: The peeling force between the display screen and the cover plate structure is greater than or equal to 18 N / cm.

26. The electronic device according to claim 24 or 25, characterized in that: Also includes a housing assembly, the housing assembly includes a first housing, a second housing and a shaft mechanism, the first housing is rotatably connected to one side of the shaft mechanism, and the second housing is rotatably connected to the other side of the shaft mechanism; The screen includes a first display area, a second display area and a third display area, the third display area is connected between the first display area and the second display area, the first display area is arranged on the first shell, the second display area is arranged on the second shell, and the third display area is arranged on the hinge mechanism.

27. Use of the glass according to any one of claims 1 to 15 or the glass prepared by the preparation method according to any one of claims 16 to 20 in cover structures, screens, and electronic devices.

Citation Information

Patent Citations

  • Cover member

    CN107074639A

  • Chemically strengthened glass

    WO2022039056A1

Cited By

  • Glass and preparation method therefor and use thereof, cover plate structure, and electronic device

    EP4600227A1

  • Glass and preparation method therefor and use thereof, cover plate structure, and electronic device

    WO2024113959A1